Professional interrelation and continuity of cares - José Ramón Martínez Riera (Universidad de Alicante, 2012)
The benefit of cares needs a Professional Interrelation that facilitates the suitable and necessary continuity. Throughout of this work is analyzed the concept of Interrelation and its necessity, and also the difficulties that prevent their development. The welfare levels, the sanitary professionals, the Organization, the Community and the user and his family, become pieces nails to reach a suitable Continuity of the cares that happens necessarily through the Professional Interrelation. The Nurses as pieces nail of the dilemma caring of to cure, acquire a greater protagonism in this necessity versus difficulty of the Professional Interrelation, which forces to consider changes in the attitudes and aptitudes that favor the continuity of the cares that the Community demands.